Danger, keep out! Trade union rights of entry during the COVID-19 pandemic. (2nd January 2023) - McFarlane, Katherine
ABSTRACT: The closures and restrictions imposed at workplaces around Australia in response to the COVID-19 pandemic have raised unprecedented issues for trade unions seeking to exercise rights of entry in accordance with Part 3–4 of the Fair Work Act 2009 (Cth). Section 491 requires that union officials seeking to exercise a statutory right of entry comply with any 'reasonable request' by an occupier about an occupational health and safety (OHS) requirement that applies to the premises. This had led to disputes about the appropriateness of requirements imposed by employers to mitigate the risk of COVID-19 infection and transmission. This paper will discuss three recent Fair Work Commission (FWC) decisions which consider the reasonableness of requests limiting entry to premises in this context. Although the cases had different outcomes, the FWC's findings demonstrate how an employer's OHS obligations relating to COVID-19 will be weighed against the objects of Part 3–4. Overall the FWC has taken a practical and nuanced approach to such disputes, and expected some cooperation between employers and unions. The limited scope of these decisions does, however, leave some questions relating to rights of entry during the pandemic unanswered.